A nightmare on Elm Street 2. Freddy's revenge [videorecording (DVD)] . - Patton, Mark, 1964-; Gulager, Clu; Lange, Hope; Myers, Kim, 1966-; Englund, Robert, 1947-; Chaskin, David (Nightmare on Elm Street collection., 1999)
A new kid on Elm Street is being haunted every night by gruesome visions of the deadly dream stalker.